Tanggung Jawab Pemasyarakatan Terhadap Hak Atas Kebebasan Beribadah Narapidana Muslim (Studi Di Lembaga Pemasyarakatan Kelas IIB Jombang) - Zakiy Bima Kusuma Aliyan (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTThere are local regulations regarding the rights of citizens exercise in accordance with the religious, islam is the religion of dominant country because a number of the most people .Everyone free people to run , no more getting ganguan or disrupt their nets worship no exception for an inmate .Are equal as indonesian citizens .Personality spiritual guidance in the form of islam in a correctional institution is disenchant many prisoners , make them aware of and did not want any more repeated crimes .But was running the religious right is fairly for every muslim prisoners , whether any prisoners have freedom to worship , to depart from this writers with penelitianya who uses the interpretive in data obtained from the descriptive verbal , observation and in use.Keywords : The right to freedom of worship , convicts , human rights